Research advances in cryopreserved preparations of mesenchymal stem cells: technical innovations, application challenges, and quality control - Wang, Yuhao; Yang, Kexin; Yuan, Shengmeng; Huo, Fangjun; Yang, Chao; Tian, Weidong (Frontiers in Bioengineering and Biotechnology, 2026)
Although mesenchymal stem cells (MSCs) are among the most promising cell types for regenerative medicine, the lack of mature “off-the-shelf” cryopreserved preparations limits their widespread clinical application. This represents a critical bottleneck and an often-underestimated complication of the cryopreservation process, which leads not only to significant reduction in viable cell yield but also to subtle yet consequential perturbations in therapeutic function. This review distinguishes itself by critically synthesizing recent advances through the lens of the integrated “vial-to-vein” pathway, emphasizing how cryopreservation-induced attrition of functional potency—particularly in immunomodulation and paracrine signaling—compromises clinical efficacy. We systematically analyze the evolution beyond conventional dimethyl sulfoxide (DMSO)-based media towards next-generation, bioinspired cryoprotectants and storage strategies designed to safeguard these critical biological attributes. We then review the cryopreservation effects on MSCs morphology, surface marker consistency, and multipotent differentiation as well as their fundamental immunomodulation. Subsequently, the review consider the efficiency of cryopreserved MSCs in different disease models like cardiovascular diseases — respiratory diseases and chronic kidney disease. Finally, we discuss the pivotal transition in quality control, arguing for a multi-pillar paradigm that integrates precise molecular identity testing with clinically relevant functional potency assays tailored to specific indications. Crucial in the pursuit of this integrated understanding is to ensure a set of consistent, reliable and coherent properties by which next-generation MSCs therapies can be evaluated. Yet correlating these in vitro metrics with clinical efficacy remains the single greatest hurdle.